A Foxo/Notch pathway controls myogenic differentiation and fiber type specification - Kitamura, Tadahiro (American Society for Clinical Investigation, 2007)
Forkhead box O (Foxo) transcription factors govern metabolism and cellular differentiation. Unlike Foxo-dependent metabolic pathways and target genes, the mechanisms by which these proteins regulate differentiation have not been explored. Activation of Notch signaling mimics the effects of Foxo gain of function on cellular differentiation. Using muscle differentiation as a model system, we show that Foxo physically and functionally interacts with Notch by promoting corepressor clearance from the Notch effector Csl, leading to activation of Notch target genes. Inhibition of myoblast differentiation by constitutively active Foxo1 is partly rescued by inhibition of Notch signaling while Foxo1 loss of function precludes Notch inhibition of myogenesis and increases myogenic determination gene (MyoD) expression. Accordingly, conditional Foxo1 ablation in skeletal muscle results in increased formation of MyoD-containing (fast-twitch) muscle fibers and altered fiber type distribution at the expense of myogenin-containing (slow-twitch) fibers. Notch/Foxo1 cooperation may integrate environmental cues through Notch with metabolic cues through Foxo1 to regulate progenitor cell maintenance and differentiation.